Penistaan Agama dalam Tafsir Ayat Al Quran - Wandi Wandi; Dwika Putri Adinda; Rahma Salmiarti; Azil Hanifa Azzahra (Universitas Palangka Raya, 2025)
Blasphemy in the context of Quranic exegesis is a highly relevant topic in religious and Islamic legal discourse. This paper aims to examine the concept of blasphemy from the perspective of Quranic interpretation, as well as how the interpretation of verses related to religious insults can influence the understanding of Muslims regarding the limits of freedom of speech and religious practices. This research utilizes a qualitative method with a contextual exegesis approach to analyze the verses often associated with blasphemy. The findings indicate that the interpretation of these verses heavily depends on the historical and social context, as well as the jurisprudential approach used in understanding Islamic laws. Furthermore, this paper highlights the importance of tolerance and respect for differences in faith when addressing issues of blasphemy, and the need for a wise approach in interpreting sacred texts. Finally, the paper suggests the necessity of interfaith dialogue and a more inclusive approach in discussing issues of blasphemy to avoid conflict and maintain social harmony.